2007
DOI: 10.1598/rt.61.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Comic Strips as a Text Structure for Learning to Read

Abstract: Teachers can use comics for reading instruction by capitalizing on their colorful graphic representation. Technology and reading are wed during the use of the Internet, and readers must rely on their visual literacy skills–a group of vision competencies people can hone for comprehension. This article reports on strategies for developing visual literacy skills by using comic strips. Comic strips provide a quick, concise way to teach and apply reading skills for practice or remediation. Suggestions for using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
17

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 6 publications
0
25
0
17
Order By: Relevance
“…Because they use few words to summarize thoughts and events, teachers can use them to teach inference. Teachers can begin by reading aloud a comic strip to the class, model how to infer meaning from the brief text and the graphic, and then discuss the meaning of the strip (McVicker, 2007). In addition, because they are fun and students can relate to them, comic strips are likely to get the attention of the students.…”
Section: Sociocultural Literacy Practices and Reading Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Because they use few words to summarize thoughts and events, teachers can use them to teach inference. Teachers can begin by reading aloud a comic strip to the class, model how to infer meaning from the brief text and the graphic, and then discuss the meaning of the strip (McVicker, 2007). In addition, because they are fun and students can relate to them, comic strips are likely to get the attention of the students.…”
Section: Sociocultural Literacy Practices and Reading Developmentmentioning
confidence: 99%
“…Besides using comic strips as an alternative to traditional text structure such as narrative texts (storybooks), non-narrative texts (nonfiction), and poetry (McVicker, 2007), Moje (2000) proposed that graffiti writing be acknowledged as a literacy approach for developing pedagogies for marginalized students. Graffiti writing, one of many unsanctioned literacy practices of gang-connected students, could be used as a meaning-making, expressive, and communicative tool.…”
Section: Sociocultural Literacy Practices and Reading Developmentmentioning
confidence: 99%
“…Representing an information using images, specifically with comic strips, increases the attention, comprehension, recall and adherence ability in human subjects. This correlation between the images and the memory construct was used in the implementation of our technique [16,17,18]. Knowledge learned implicitly are not consciously accessible to or may not be described explicitly by the person being trained [13,14,15,19,20].…”
Section: Rubber-hose Attacks and Existing Techniquesmentioning
confidence: 99%
“…When presented to students, each section of the GVVP template is missing one element (see Figure 2), and different templates can contain one of three possible iterations for each noun (see Figure 3). The style of a GVVP template is intended to resemble the format of a comic strip, as suggested by McVicker (2007) as an effective and visually appealing method to teach vocabulary to students. A preliminary investigation of GVVP indicated that the strategy resulted in a moderate effect size for participants in grades 5-12.…”
Section: Figure1mentioning
confidence: 99%